Collocations in Essay Writing by Foreign Arabic Language Learners: Language Acquisition - Garba, Mahmud Abubakar (Al-Ḍād Journal, 2024)
Collocations are an important aspect of foreign language learning; Because it greatly enhances linguistic proficiency, especially in written or spoken expression. The current study aims to explore the effect of collocations in improving written expression among learners of Arabic as a foreign language in Nigeria. Employing a quasi-experimental design, the research endeavors to assess the influence of collocations on the advancement of written expression among third-year undergraduate students enrolled in the essay writing course in the Arabic Department during the academic year 2022/2023 at Umar Musa Yar’adua University Katsina, Nigeria. The selection of participants for this essay writing exercise was conducted through purposive sampling, resulting in a sample size of seventy students. These participants were then divided into two groups: an experimental group consisting of 35 students(n=35) and a control group also consisting 35 students(n=35). Data collection was executed through pre- and post-test essay writing tasks, with subsequent data analysis relying on inferential statistics. The results indicated that there were statistically significant differences at the significance level (p=000) between the two groups in the post-test. This means that the results of the study indicate an improvement in the performance of the experimental group in terms of the content of writing, use of vocabulary in the form of collocations, and the use of language, compared to the control group in the post-test. Therefore, it can be said that collocations have an impact on the development of written expression in the form essay writing for learners of Arabic as a foreign language at Umar Musa University Katsina, Nigeria. Key Words: Collocations, Foreign language learning, lexical Approach, Essay Writing, grammar and Translation